A methodical gamut approach for analytical review of BDS campaign and Palestinian harmony - Nor, M.R.M.; Kashif, L.; Ismail, M.N.; Nazri, M. (2016)
This paper analysis and appraises the Boycott, Divestment, Sanctions (BDS) campaign against Israel. First, it adumbrates the different conflicts with appearance and eminence of the BDS campaign. Then, it elucidates the BDS strategy, particularly the boycott. Next, the paper elaborate by recognized the campaign’s power and promise with relation to the discourse of Palestinian- Israeli politics. More unequivocally, the campaign is powerful because it is a networked contestation of the discursive rules that involve symmetry be posited between Palestinians and Israel.